Dissolved organic carbon sorption dynamics in tidal marsh soils. Issue 1 (29th September 2020) - Pinsonneault, Andrew J.; Neale, Patrick J.; Tzortziou, Maria; Canuel, Elizabeth A.; Pondell, Christina R.; Morrissette, Hannah; Lefcheck, Jonathan S.; Megonigal, James Patrick
Abstract: Coastal wetlands are significant sources of dissolved organic carbon (DOC) to adjacent waters and, consequently, exert a strong influence on the quantity and quality of DOC exported to the coastal oceans. Our understanding of the factors that control the exchange of DOC at the tidal marsh‐estuarine interface, however, remains limited. We hypothesize that tidal marsh soils act as a regulator and that their physical characteristics, such as organic carbon content and mineral phase composition, are key controls on DOC exchange between soil surfaces and both surface and interstitial waters. To test this hypothesis, we generated traditional Langmuir sorption isotherms using anaerobic batch incubations of four tidal wetland soils, representing a range of soil organic carbon content (1.77% ± 0.12% to 36.2% ± 2.2%) and salinity regimes (freshwater to mixoeuhaline), across four salinity treatments. Results suggest that the maximum soil sorption capacity and DOC binding affinity increase and decrease with greater salinity, respectively, though the enhancement of maximum soil sorption capacity is somewhat mitigated in soils richer in poorly crystalline iron minerals. Initial natively sorbed organic carbon showed a significant positive correlation with soil specific surface area and K showed a moderate yet significant positive correlation with poorly crystalline iron mineral content. Taken together, these results point to a strong mineralogical control on tidal marsh sorption dynamics and a complex physicochemical response of those dynamics to salinity in tidal marsh soils.